Artistic career of the painter Juan Bautista Planeta in Lima. New news and attribution - Chuquiray, Javier (2019)
It reviews the known artistic trajectory of the painter Juan Bautista Planeta (Lima, 1626-1642), by giving to know unpublished information about biographical aspects —such as the confirmation of his Italian origin and his priestly ordination— and historical-artistic —such as his workshop that was kept until his death. In addition, it is proposed two attributions to his authorship, with documentation: the mural painting of the chapel of captain Villegas and a sketch of St. Jerome. The knowledge of his work, related to Italian Mannerism, contributes to the panorama of painting from Lima of the seventeenth century, time of transition between Mannerism and Baroque.